The Music and (dis)harmony of (anti)utopia in Samuel Butler’s Erewhon - Françoise Dupeyron-Lafay (Cahiers Victoriens et Edouardiens)
Unlike architecture, music is mostly a marginal or infrequent aspect of utopian literature, though usually invested with solely positive connotations. It is however particularly prominent in Samuel Butler’s Erewhon but it is only described negatively, as unpleasant, discordant and even cacophonous. This is where Butler’s radical originality lies: firstly in this diversion of the laudatory, spiritualized conception of music and of its utopian associations; and secondly in the (re)appropriation of music for satiric and anti-utopian purposes. After a brief survey of the usual role and connotations of music in utopias, this paper will focus on its value and symbolism before the narrator’s stay in Erewhon. It will then address its representation in the unknown land that collapses the literal (acoustic) and social meanings of discordance with unpleasant or cacophonous music as the index to a dysfunctional world and its ethical flaws. Lastly, the article will deal with the narrator’s unstable stance and views, which, together with the generic and tonal hybridity of the text and its ironic logic, alternating between satire and (anti)utopia, make the novel go through a series of perplexing ideological fluctuations. Like the cacophonous music of Erewhon, the message conveyed is ultimately ambiguous and at times discordant.